Polyhydroxyalkanoate of Actinomycetes native from Colombian soils - Franco-Correa, Marcela (2009)
The polyhydroxyalkanoates (PHA) are considered as source of renewable-resource-based, biodegradable materials and plastics of a wide range industrial uses, but high production costs impede large-scale implementa- tion. In this paper, we induced the production of polyhydroxyalkanoates (PHA) in actinomycetes isolated from Colombian soil, the microorganism with highest production and accumulation of biopolymer was isolated and identified. With Nile blue dye, we determined in three of the ten strains isolated, the presence of intracellular fluorescent granules type polyhydroxyalkanoate. The three strains were cultured for obtained significant amounts of PHA. The strain named 7F had the highest production. After purification, identification and quantification we determined a yield of 27.48% in dry weight, which means a good productivity. This strain was identified as Streptomyces subrutilus, though biochemical’s reactions and Gene Bank.